The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.4028/p-d1j831
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Rhodamine B Dye by Nanocomposites: A Review

Abstract: Pollution by textile dyes on waterbodies is an issue for both human health and the environment. To remove/degrade dyes, many approaches (coagulation, membrane separation, and adsorption) have been investigated. However, the use of semiconductor-assisted materials in conjunction with sustainable solar energy has emerged as a possible solution to the problem. Although single component photocatalysts have been tested, composites of semiconductor materials are being employed owing to their low efficiency and stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…The quantity of nanocomposites as nanocatalysts is another important parameter in assessing the effect of the photocatalyst process on dye removal efficiency. The effect of the photocatalyst γ-Fe 2 O 3 Np/TiO 2 nanocomposite amount on photodegradation of OG was investigated by varying the γ-Fe 2 O 3 Np/TiO 2 amount to 50, 70, 80, 90, and 100 mg in contact with 100 mL of OG solution (5 mg L –1 ), with same experimental conditions and under LED irradiation, and the obtained results are reported in Figure . It has been observed that the loading of photocatalysts has a significant impact on OG degradation.…”
Section: Resultsmentioning
confidence: 99%
“…The quantity of nanocomposites as nanocatalysts is another important parameter in assessing the effect of the photocatalyst process on dye removal efficiency. The effect of the photocatalyst γ-Fe 2 O 3 Np/TiO 2 nanocomposite amount on photodegradation of OG was investigated by varying the γ-Fe 2 O 3 Np/TiO 2 amount to 50, 70, 80, 90, and 100 mg in contact with 100 mL of OG solution (5 mg L –1 ), with same experimental conditions and under LED irradiation, and the obtained results are reported in Figure . It has been observed that the loading of photocatalysts has a significant impact on OG degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the common techniques used to characterize nanocomposites are XRD, SEM, EDS, TEM, TG, DSC, and FTIR. To investigate the phases present in the nanocomposites XRD is preferred [51][52][53][54][55]. To study the morphology of the nanocomposites SEM is the best choice.…”
Section: Resultsmentioning
confidence: 99%
“…It is a persistent organic pollutant that can remain in the environment for long periods, posing a risk to aquatic life and humans. Rhodamine B is toxic to humans and can cause skin irritation, eye irritation, respiratory problems, digestive problems, and cancer [3,4]. Rhodamine B is resistant to biodegradation due to its stable structure, so it persists in natural environments and wastewater systems after use.…”
Section: Introductionmentioning
confidence: 99%